2014
DOI: 10.3389/fpsyg.2014.00927
|View full text |Cite
|
Sign up to set email alerts
|

Children’s mental time travel during mind wandering

Abstract: The prospective bias is a salient feature of mind wandering in healthy adults, yet little is known about the temporal focus of children’s mind wandering. In the present study, (I) we developed the temporal focus of mind wandering questionnaire for school-age children (TFMWQ-C), a 12-item scale with good test–retest reliability and construct validity. (II) The criterion validity was tested by thought sampling in both choice reaction time task and working memory task. A positive correlation was found between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 56 publications
2
40
3
Order By: Relevance
“…68 ). As certain subtypes of spontaneous cognitive processes are detectable in time-varying functional connectivity measurements 68 , it could be hypothesized that part of our results might pertain to the age-related changes in the occurrence of mind wandering episodes and in the content/type of spontaneous cognitive processes observed from childhood to young adulthood and from young to late adulthood 63,[69][70][71][72][73][74][75][76][77] . Further studies should investigate this critical issue.…”
Section: Results Of Static Rsfc Analyses Are In Line With Previous Stmentioning
confidence: 95%
“…68 ). As certain subtypes of spontaneous cognitive processes are detectable in time-varying functional connectivity measurements 68 , it could be hypothesized that part of our results might pertain to the age-related changes in the occurrence of mind wandering episodes and in the content/type of spontaneous cognitive processes observed from childhood to young adulthood and from young to late adulthood 63,[69][70][71][72][73][74][75][76][77] . Further studies should investigate this critical issue.…”
Section: Results Of Static Rsfc Analyses Are In Line With Previous Stmentioning
confidence: 95%
“…Similar issues concerning the need for equating the difficulty of ongoing (vigilance) tasks in different age groups arise in relation to studying spontaneous future (and past) thoughts in children, and especially in very young children who may also have difficulties in meta-awareness or noticing and reporting spontaneous thoughts-more so than older adults (e.g., see Chen, 2013, cited in Ye, Song, Zhang, & Wang, 2014. Because of these difficulties, there are currently less than a handful studies on mind-wandering in older children and adolescents (e.g., Ye et al, 2014;Van den Driessche et al, 2017;Stawarczyk et al, 2014;Zhang, Song, Ye, & Wang, 2013), with virtually no developmental studies on children's spontaneous future thinking. The studies reported by McCormack et al and Caza and Atance in this issue are therefore starting to fill this gap in the literature by developing and testing new methods that have resulted in important new insights on children's spontaneous future thinking ability and its relationship with its voluntary counterpart.…”
Section: Development Across the Life Spanmentioning
confidence: 99%
“…Moreover, few studies have examined mind-wandering among Chinese (some examples include Song & Wang, 2012;Ye, Song, Zhang, & Wang, 2014). Specifically, Song and Wang (2012) used the experience-sampling method to collect mind-wandering experiences among Chinese undergraduates and Ye et al (2014) investigated the temporal focus of mind-wandering in a pupil's sample.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, Song and Wang (2012) used the experience-sampling method to collect mind-wandering experiences among Chinese undergraduates and Ye et al (2014) investigated the temporal focus of mind-wandering in a pupil's sample. Therefore, an appropriate Chinese scale does not exist to measure the trait levels of mind-wandering among adolescents.…”
Section: Introductionmentioning
confidence: 99%